THE ROLE OF SELF-EFFICACY AND FAMILY SUPPORT IN STABILIZING BLOOD PRESSURE OF PATIENTS WITH HYPERTENSION - Erni Tri Indarti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Hypertension is a health problem for the majority of people in Indonesia. The Efforts to reduce the incidence rate of hypertension and controling blood pressure by changing the healthy lifestyle and by being in taking. To realize healthy lifestyle and behavior of hypertension, self-efficacy and support of the family as well as health care cooperation with the parties, the family, and society are required. The purpose of this research to know if self-efficacy and family support stabilizing blood pressure of patients with hypertension. This research is a pre-experimental research with One-Group Pre-Post test design approach. The study was conducted in 50 people with the stratified random sampling technique in Ketawang Village, Gondang Districtor 8 weeks. Measurement of the blood pressure was the Spignomanometer merk Onemed was given before and after the patients were given counseling self-efficacy and family support. The data was analyzed SPSS 21 Wilcoxon test. The Statistical test results obtained p value 0.000 to sistole and diatole so that there is a meaningful that self-efficacy counseling and family support stabilizing blood pressure of patients hypertension. Self-efficacy counseling and family support controling blood pressure for patients with hypertension, so they needs to be developed to reduce hypertension complications.